Islet autoantibody profiles associated with higher diabetes risk in Lithuanian compared with English schoolchildren. (26th October 2020) - Long, A. E.; Caygill, C. H.; Gillespie, K. M.; Marčiulionytė, D.; Williams, A. J. K.
Summary: During a 15‐year period, the incidence of type 1 diabetes has doubled in Lithuania, while increasing by a third in England; however, England still has a higher incidence. Analysis of sera collected from non‐diabetic schoolchildren from Lithuania and England more than 20 years ago showed a similar number of multiple autoantibody‐positive schoolchildren between the populations, but a higher prevalence of islet antigen‐2 autoantibodies (IA‐2A) in English schoolchildren. We aimed to use recently developed, more specific islet autoantibody tests to characterize differences in humoral autoimmunity between these two general population cohorts in greater detail. Samples from 88 Lithuanian and 133 English schoolchildren previously found islet autoantibody‐positive were selected for measurement of additional islet autoantibodies by radioimmunoassay. Samples were tested for autoantibodies to zinc transporter 8 (ZnT8A), GAD (96–585), the protein tyrosine phosphatase region of islet antigen‐2 (PTPA) and the related IA‐2βA, while autoantibodies to IA‐2A were reassayed using the current harmonized method. IA‐2‐related autoantibodies PTPA (0·13 versus 0·45%, P  = 0·027) and IA‐2βA (0 versus 0·35%, P  < 0·001), but not IA‐2A measured using the harmonized method, were less common in Lithuanian compared to English schoolchildren. Lithuanian schoolchildren who were islet autoantibody‐positive were positive for fewer biochemical autoantibodies compared with English schoolchildren ( P  = 0·043). Background rates of islet autoimmunity in childhood differ subtly between countries, which have different incidences of type 1 diabetes. The optimal screening strategy (age and combination of markers) for detection of islet autoimmunity may vary between countries, dependent upon the pattern of autoantibodies found in the general population. Abstract : This study used recently developed, more specific islet autoantibody tests, to characterise differences in humoral autoimmunity between two childhood general population cohorts, from Lithuania and England, in greater detail. The new data support our previous observation that certain aspects of the autoantibody profile associated with more rapid progression, including responses related to IA‐2A, are different in Lithuanian compared with English schoolchildren.